INFERENSI DALAM KUMPULAN CERPEN MEMBACA HANG JEBAT KARYA TAUFIK IKRAM JAMIL - Alvina '; Charlina '; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Learning a language through pragmatics is that one can speak the word about the meaning that people mean, their assumptions, their intentions or their purpose and the types of actions. Inference is a form of drawing conclusions that struggle through the context. The formulation of the problem of what is the inference in the Collection of Short Stories Reading Hang Jebat created by Taufik Ikram Jamil. Aims to describe inference in the Collection Short Story of Reading Hang Jebat created by Taufik Ikram Jamil. The benefits of research are theoretically and practically described. So that the definition of operational inference is a process of drawing conclusions through the expression based on context and inference in a Collection of Short Stories Read Hang Jebat is a process of drawing conclusions through context-based phrases and using implicatures. The study theory used is Abdul Chaer, Charlina Dan Mangatur Sinaga, Louise Cummings, Halliday, Hamid Hasan Lubis, Kridalaksana, Milles, Moleong, Mulyana, Nadar, Parera, Priyatni, Rahardi, Scriffrin, Suyanto, Wagiman, And Yule George. This study was conducted from February 2017 to June 2017. The data looked at the types of inference and data sources that are the Concatenation Reading Hang Jebat created by Taufik Ikram Jamil. Data collection is done by reading, classifying, labeling and analysis. Data analysis techniques include data reduction, data presentation and conclusion drawing. The data found in 92 data includes: 39 in deductive inference, 41 in elaborative inference and 12 in conversation inference. Then, this study has a conclusion of the benefits of inference, inference state, and inference in literary texts. Recommendations can improve understanding and reference materials on inferences.Keywords: Inference, Collection of Short Stories.